Anaesthetic efficacy of intraligamentary injection techniques on mandibular molars diagnosed with asymptomatic irreversible pulpitis: A retrospective study. (25th August 2016) - Lin, Shaul; Wigler, Ronald; Huber, Ronen; Kaufman, Arieh Y.
Abstract: The objective of this study was to evaluate the success rate of intraligamentary injections (ILI) using a two‐ or four‐site injection technique. One hundred and fifty‐one mandibular molars diagnosed with asymptomatic irreversible pulpitis received ILI at the mesiobuccal and distobuccal aspects of the roots. Patients who experienced pain when the access cavity was performed received additional supplemental ILI in the mesiolingual and distolingual aspects. Pulpal anaesthesia was considered successful when complete analgesia was achieved. The data were analysed by means of the Fisher's exact and Pearson's chi‐square tests. IL anaesthesia was successful for 92.1% of the teeth. Forty‐eight teeth (31.8%) were sufficiently anaesthetised using the two‐site ILI and 91 teeth (60.3%) following supplemental IL anaesthesia in two more sites. The results of this study indicate that the use of four‐site IL injections as a primary anaesthetic technique may be considered a favourable alternative to the common IANB.